2007
DOI: 10.1111/j.1365-2133.2006.07526.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycosis fungoides: a dermatological masquerader

Abstract: Mycosis fungoides (MF), a low-grade lymphoproliferative disorder, is the most common type of cutaneous T-cell lymphoma. Typically, neoplastic T cells localize to the skin and produce patches, plaques, tumours or erythroderma. Diagnosis of MF can be difficult due to highly variable presentations and the sometimes nonspecific nature of histological findings. Molecular biology has improved the diagnostic accuracy. Nevertheless, clinical experience is of substantial importance as MF can resemble a wide variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 113 publications
0
90
0
13
Order By: Relevance
“…6 A second, more recent, study also showed significantly higher mortality among patients with folliculotropic MF. 13 In particular, overall survival was much lower among patients with early-stage (ie, stage IIA) folliculotropic MF (41%) than comparable patients with early-stage classic MF (91%). 14 These data also indicate that when compared with individuals with tumor-stage MF, patients with folliculotropic disease have a similar or potentially worse prognosis, suggesting an intrinsic biologic difference.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…6 A second, more recent, study also showed significantly higher mortality among patients with folliculotropic MF. 13 In particular, overall survival was much lower among patients with early-stage (ie, stage IIA) folliculotropic MF (41%) than comparable patients with early-stage classic MF (91%). 14 These data also indicate that when compared with individuals with tumor-stage MF, patients with folliculotropic disease have a similar or potentially worse prognosis, suggesting an intrinsic biologic difference.…”
Section: Discussionmentioning
confidence: 98%
“…12 In patients with more extensive disease, the affected skin may show hyperkeratosis, poikiloderma atrophicans vasculare, erythroderma, or palmoplantar keratoderma. 13 Histologically, the classic features of syringotropic CTCL are hyperplastic eccrine glands and eccrine ducts surrounded by a dense, syringotropic infiltrate of atypical lymphocytes with characteristic cerebriform nuclei. 6 However, this type of infiltrate is not limited to syringotropic CTCL and can occasionally be seen in folliculotropic MF.…”
Section: Discussionmentioning
confidence: 99%
“…We wish to include the remaining papers which cite PEO and have not been used for this paper but were nonetheless taken into consideration [112,113,114,115,116]. We also thank Dr. Masahiro Amano for help in translating Japanese references.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…In rare instances early MF can be a great masquerader of common skin diseases impeding appropriate diagnosis. 2 We present a 69-year-old male with a 3-month history of slowly progressing eczema on his hands and feet accompanied by generalized itch. His past medical history included benign prostatic hyperplasia, hypothyreosis and cardiac arrhythmia treated with L-thyroxine, lercanidipine, flecainide, rivaroxaban and vitamin B12.…”
mentioning
confidence: 99%